Political dynasties and poverty: Resolving the “chicken or the egg” question - Mendoza, Ronald U (Archīum Ateneo, 2013)
"Political dynasty" refers to the situation wherein members of the same family are occupying elected positions either in sequence for the same position, or simultaneously across different positions. In the Philippines, political dynasties are prevalent in areas with more severe poverty. Two explanations for this situation have been proposed: poverty brings about political dynasties, or political dynasties engender poverty. These arguments suggest that the relationship between political dynasties and poverty can be treated as an empirical question. (So which one is the chicken, and which one is the egg?) In order to examine the direction of causality between political dynasties and poverty, this paper turns to provincial-level data from the Philippines and develops novel metrics on political dynasties: the shares of total positions occupied by dynastic politicians, of the largest dynastic clan as regards total positions, and of dynastic concentration inspired by the industrial concentration literature. To address endogeneity, instrumental variables for poverty are used, consisting of indicators for rainfall and the geographical distance to Manila (the Capital). The results we find are striking: poverty entrenches political dynasties; education appears to have no bearing on political dynasties; and the media affect only the largest political dynasties. There is less evidence that political dynasties bring about poverty.